Pengaruh Matakuliah Kewirausahaan dan Motivasi Berwirausaha Terhadap Minat Menjadi Wirausahawan dikalangan Mahasiswa Prodi Manajemen Angkatan 2023 Universitas Negeri Medan - Hasyim Hasyim; Afifah Nida Suhailah Boru Dalimunthe; Jekson Sihombing; Tasya Chintain Simanjuntak (MANAJEMEN, 2026)
This study aims to examine the effect of Entrepreneurship Courses and Entrepreneurial Motivation on students Entrepreneurial Intention at Universitas Negeri Medan. The study employed a quantitative approach with a sample of 48 students and analyzed the data using multiple linear regression. The results show that, simultaneously, both variables have a positive and significant effect on entrepreneurial intention (F = 27.228; p < 0.001), with a coefficient of determination (R²) of 0.548. Partially, Entrepreneurship Courses have a positive and significant effect (β = 0.413; p = 0.008), while Entrepreneurial Motivation has a more dominant influence (β = 0.489; p < 0.001). These findings indicate that intrinsic motivation plays a more crucial role in enhancing students’ entrepreneurial intention, although entrepreneurship education also contributes positively.